PENGARUH LATAR BELAKANG PENDIDIKAN DAN MASA KERJA TERHADAP KINERJA GURU RAUDHATUL ATHFAL - Nasution, Masnun Zaini; Darmayanti, Nefi (Universitas Medan Area, 2011)
The purpose of this study was to see the influence of educational background and years of teacher performance Raudhatul Athfal in Medan. The proposed hypothesis of the study, which reads:Â There was no effect of the educational background and work together on the performance of the Athfal Raudatul teacher in Medan. Based on data analysis using a Varian Analysis of Two Path, then obtained the following results: 1). There is a very significant influence of educational background on performance. These results are known by looking at the value or coefficient difference ANAVA FA = 8.978 with p <0.010. 2). There is a significant influence on the performance of the work. These results are known by looking at the value or coefficient difference ANAVA FB = 4.131 with p <0.050. 3). There is no influence of the educational background and work together on performance. These results are known by looking at the value or coefficient difference ANAVAÂ = 0.267 with p> 0.050. The teacher who has a service life of between 4 to 10 years had a higher performance with the performance of the average value of 201.594 as compared with teachers who have tenure over 10 years with an average value of 196.926 and the performance of teachers who have a service life of between 1 to 3 years with an average value of the performance of 191.538.